Induction of Cytoplasmic dsDNA and cGAS-STING Immune Signaling After Exposure of Breast Cancer Cells to X-ray or High-Energetic Carbon Ions - Cristina Totis, MSc; Nicole B. Averbeck, PhD; Burkhard Jakob, PhD; Maik Schork, PhD; Gaia Volpi, MSc; Dennis F. Hintze, BSc; Marco Durante, PhD; Claudia Fournier, PhD; Alexander Helm, PhD (Advances in Radiation Oncology)
Purpose: Radiation therapy can trigger activation of the cyclic GMP-AMP synthase (cGAS)- Stimulator of interferon genes (STING) axis via cytoplasmic dsDNA fragment induction. The activation of cGAS-STING initiates innate immune signaling mediated by interferon type I that can contribute to eradicate the malignancy. The effect was shown to depend on the fractionation scheme employed. We hypothesized that the innate immune response can also depend on radiation quality because densely ionizing radiation, such as carbon ions, have different effects on DNA lesion quality. Methods and Materials: We exposed an in vitro 4T1 breast cancer model to either photons or carbon ions and measured the clonogenic survival of cells with the colony-forming assay. The occurrence of cytosolic dsDNA fragments was assessed via immunofluorescence, whereas the expression and release of interferon-β by quantitative reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assay. Bulk RNA sequencing was used to investigate global radiation-induced changes in gene expression. Results: We show here that carbon ions induced a significantly higher yield of cytosolic dsDNA fragments per unit dose as compared to photons. The higher efficiency also translated in expression and release of interferon-β by the tumor cells. The rate of cytoplasmic dsDNA foci as well as interferon-β release increased with doses up to 20 Gy and no differences for a fractionation scheme (3 × 8 Gy) were found as compared to the single high doses (20 or 24 Gy) of photons. Conclusions: In conclusion, we found that the release of interferon-β after radiation increases with the radiation dose up to 20 Gy and that carbon ions have the potential to elicit a strong innate immune signaling.